1995
DOI: 10.1111/j.1442-2042.1995.tb00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ and Interindividual Variation in the Pharmacokinetics of Tacrolimus (Fk506) in Kidney Transplant Recipients—importance of Trough Level as a Practical Indicator

Abstract: We conclude that trough level is a practical acceptable indicator of the blood levels of tacrolimus, and can be used to monitor blood concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
1
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 5 publications
6
38
1
1
Order By: Relevance
“…The χ 2 test was used to analyze differences in the frequencies between Sicilian and non-Sicilian subjects. The allele and genotype frequencies of the CYP3A5 and ABCB1 polymorphisms were assessed for deviation from the Hardy-Weinberg equilibrium using the χ 2 test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The χ 2 test was used to analyze differences in the frequencies between Sicilian and non-Sicilian subjects. The allele and genotype frequencies of the CYP3A5 and ABCB1 polymorphisms were assessed for deviation from the Hardy-Weinberg equilibrium using the χ 2 test.…”
Section: Discussionmentioning
confidence: 99%
“…Achieving the desired target blood concentrations as soon as possible after transplantation is crucial to avoid rejection or excessive immunosuppression and to limit significant dose-related adverse reactions such as nephrotoxicity, neurotoxicity and hyperglycemia (1). To date, trough whole blood concentration (C 0 ) represents the most common parameter used for the therapeutic monitoring of tacrolimus; it is measured 12 h after dose administration and correlates well with the area under the concentration-time curve (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…8 However, there are large interindividual variations in the pharmacokinetics of tacrolimus from this and other studies. 9,10,13,14,16,19,20 It can be concluded that initiation of tacrolimus therapy via the intravenous route is a better method of administration. The conversion dosage cannot be calculated from preoperative oral or postoperative intravenous pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Tacrolimus displays a narrow therapeutic index and large inter-/ intra-patient variability in its pharmacokinetics. 4 Trough levels are good indicators of systemic exposure, but correlation with drug dose is poor. 5 It is important, therefore, that patients receiving tacrolimus are monitored regularly.…”
Section: Introductionmentioning
confidence: 99%